Effectiveness of Kahoot-assisted PBL on the rapid reading ability of SLB students in Nias - Epi Supriyani Siregar; Ika Purnama Sari -; Burhanuddin; Muhammad Isnaini; Mona Novita (Indonesian Journal of Educational Development (IJED), 2026)
Speed-reading ability among students with special needs remains low, with most reading below the expected standard. This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by Kahoot in improving students' speed-reading ability. A quasi-experimental design with a pretest-posttest control group was employed. The population consisted of students from five special schools (SLB) in Nias Regency. A total of 97 students were selected using purposive sampling and divided into an experimental group (n = 49) and a control group (n = 48). Data were collected through reading speed tests, observation sheets, and student engagement questionnaires. The instruments were validated prior to use. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results indicate that the PBL-Kahoot model significantly improves students' speed-reading ability. Student engagement plays a mediating role, and the model explains a substantial proportion of variance in reading performance. The intervention shows varying effectiveness across different types of special needs, with higher gains observed in certain groups. In conclusion, the integration of PBL and Kahoot effectively enhances speed reading ability through increased student engagement. It is recommended that teachers adopt technology-assisted, student-centered learning models and adapt them to students' specific needs.